Quality of life and illness perception in working and sick-listed chronic RSI patients - Sluiter, Judith K. (Springer-Verlag, 2007)
OBJECTIVE: To study differences between working and sick-listed chronic repetitive strain injury (RSI) patients in the Netherlands with respect to indices of quality of life and illness perception. METHODS: In a cross-sectional design, one questionnaire was sent to all 3,250 members of the national RSI patient association. For descriptive purposes, demographics, work status and complaint-related variables such as severity, type, duration, and extent of complaints were asked for. Indices of quality of life were assessed through seven SF-36 subscales (physical (role) functioning, emotional role functioning, social functioning, pain, mental health and vitality). A work-ability estimate and VAS scales were used to assess complaint-related decrease in quality of life. Illness perception was assessed through the brief illness perception questionnaire (IPQ-B). Working patients and sick-listed patients were identified. Tests between the two independent groups were performed and P-values < 0.01 were considered significant. RESULTS: Data from 1,121 questionnaires were used. Two-thirds of the respondents worked and one-third were sick-listed. Average duration of complaints was over 5 years in both groups. The sick-listed patients reported significantly more severe and extensive complaints than did the working patients. In addition, sick-listed patients reported significantly poorer mental health, physical (role) functioning, emotional role functioning, pain, vitality, and work-ability. With respect to illness perception, both groups showed the same concerns about their complaints, but sick-listed patients had significantly more distorted perceptions in their emotional response, identity, treatment control, personal control, timeline, and life consequences. Complaint-related decrease in quality of life was 31% in the working patients and 49% in the sick-listed patients. CONCLUSION: The study found a greater number and severe complaints among sick-listed chronic RSI patients and a considerably decreased quality of life because of their complaints. These findings may allow for a better treatment focus in the future.